2021
DOI: 10.7759/cureus.14788
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers for Incidence of Lung Cancer: A Retrospective Study

Abstract: Introduction: Angiotensin-converting enzyme inhibitor (ACEI) and angiotensin II receptor blockers (ARBs) are taken as the first treatment option for hypertensive patients. The various global trials have suggested that ACEIs and ARBs may increase risk of lung cancer; however, the results are contradictory and there is no local study available. This study is conducted to compare the incidence of lung cancers in patients on ACEIs and ARBs.Methods: This retrospective study, conducted in a major cardiology unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Based on the search strategy, 2400 records from the databases were screened, of which 392 duplicated records and 1976 records did not meet the inclusion criteria and were excluded. Finally, 11 clinical studies [12][13][14][23][24][25][26][27][28][29][30], including seven cohort studies [12,14,23,[26][27][28]30] and four case-control studies [13,24,25,29], conducted between 1988 and 2020 were included in the meta-analysis (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the search strategy, 2400 records from the databases were screened, of which 392 duplicated records and 1976 records did not meet the inclusion criteria and were excluded. Finally, 11 clinical studies [12][13][14][23][24][25][26][27][28][29][30], including seven cohort studies [12,14,23,[26][27][28]30] and four case-control studies [13,24,25,29], conducted between 1988 and 2020 were included in the meta-analysis (Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…The meta-analysis comprised a total of 13,061,226 patients, including 1,493,225 patients in the ACEI group and 11,568,001 patients in the non-ACEI group. These patients mainly resided in Asia [14,27,28], North America [23,26], and Europe [12,13,24,25,30]. Patient and study characteristics of the cohort and case-control studies are described in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, ACEIs/ARBs have shown their association with a decreased risk of lung cancer in previous studies [ 53 , 54 ]. Research articles have further indicated a lower incidence of lung cancer in ARB users than in their ACEI counterparts [ 55 , 56 ]. It has, however, been revealed that high cumulative doses of ACEIs/ARBs are associated with an elevated risk of lung cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they found that the higher the dose and longer the duration of ACEI use, the higher the incidence of lung cancer. Kumar et al ( 94 ) and Hsu et al ( 95 ) subsequent studies support this view. There are different conclusions, a 2021 study by Lee et al ( 96 ) concluded that there was no significant difference in the effect of ACEI and ARB on lung cancer.…”
Section: Commonly Used Drugs For Patients With Cardiovascular Disease...mentioning
confidence: 73%